Teachers' Challenges in Developing Learning Literacy for Students at SMPN 11 Mataram - Aditra Wahyuda; Resly Febrianti Putri; Baiq Nurhani; Bila Anggraini; Edy Herianto (al-Afkar, Journal For Islamic Studies, 2025)
The purpose of this study is to analyze the abilities of students and teachers in the teaching and learning process and to measure students including the ability to analyze and the ability to sort out an activity that increases literacy. The author also hopes that in the future each student will be able to practice and read better in order to create good literacy in their environment in terms of learning activities. With this, the method used is a quantitative method, namely a combination of data processing techniques with observation so that it produces good and good research in the future and the author also concludes that each study or observation will have limited data so that the author concludes that students who lack literacy are caused by environmental factors, themselves and the will which includes teaching methods and teaching and learning actions applied in schools and teachers will also include extra teaching and learning because this literacy is carried out by students based on their own will and abilities based on what they want so that being a teacher is the most noble thing because it is in accordance with his duties to educate those who cannot become able to so that it produces students who have noble character, good and polite speech in it and improve good literacy skills in the future.